2020
DOI: 10.5812/compreped.102108
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Surgical Complications of Ventilation Tube Insertion in Children in Central Iran

Abstract: Background: Middle ear inflammation and fluid accumulation are one of the most common childhood diseases. Untreated or chronic ear inflammation can lead to more serious complications, including hearing loss, eardrum rupture, adhesive otitis media, tympanosclerosis, temporal bone necrosis, and cholesteatoma. Ventilation tube insertion is one of the best treatments to cure these diseases. Objectives: This aimed to observe children suffering from ear inflammation who were candidates for VT insertion surgery and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
(16 reference statements)
0
1
0
Order By: Relevance
“…In accordance with our findings, Saki et al [24] found high rate of complications among children treated by ventilation tube insertion in the form of transient otorrhea (12.5%), delayed otorrhea (8.2%), tympanic membrane atrophy (27.8%) tympano-sclerosis (37.9%), and persistent perforation (2.4%). Vahedian et al 25 reported that complications related to ventilation tube insertion were otorrhea (2%), tympanosclerosis (12.2%), atrophy (6.8%), residual perforation (1.5%), and recurrent OM (3.9%).…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with our findings, Saki et al [24] found high rate of complications among children treated by ventilation tube insertion in the form of transient otorrhea (12.5%), delayed otorrhea (8.2%), tympanic membrane atrophy (27.8%) tympano-sclerosis (37.9%), and persistent perforation (2.4%). Vahedian et al 25 reported that complications related to ventilation tube insertion were otorrhea (2%), tympanosclerosis (12.2%), atrophy (6.8%), residual perforation (1.5%), and recurrent OM (3.9%).…”
Section: Discussionmentioning
confidence: 99%